2009
DOI: 10.1051/0004-6361/200912189
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of toroidal flux tubes from beneath the solar photosphere

Abstract: Context. Models of flux emergence frequently use a twisted cylindrical loop as the initial starting configuration and ignore the coupling between the radiation field and plasma. In these models, the axis of the original tube never emerges through the photosphere. Without the axis emerging, it is very difficult to form a realistic sunspot. Aims. The aim is to use a toroidal flux loop, placed beneath the solar photosphere and study whether the axis of the system emerges fully into the atmosphere. The toroidal cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 34 publications
(48 reference statements)
4
77
0
1
Order By: Relevance
“…To model the emergence of the top part of a Ω-shaped loop that is rooted much deeper in the interior, an alternative choice of initial flux tube is a toroidal shaped loop. Hood et al (2009) andMacTaggart and describe how to construct an initial toroidal loop. Consider a toroidal flux tube, with the major radius of the torus, R 0 , larger than the minor radius, d. The form of the magnetic field to leading order in an expansion in powers of d/R 0 is based on the cylindrical model.…”
Section: Initial Sub-photospheric Magnetic Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…To model the emergence of the top part of a Ω-shaped loop that is rooted much deeper in the interior, an alternative choice of initial flux tube is a toroidal shaped loop. Hood et al (2009) andMacTaggart and describe how to construct an initial toroidal loop. Consider a toroidal flux tube, with the major radius of the torus, R 0 , larger than the minor radius, d. The form of the magnetic field to leading order in an expansion in powers of d/R 0 is based on the cylindrical model.…”
Section: Initial Sub-photospheric Magnetic Fieldmentioning
confidence: 99%
“…In the model by Hood et al (2009), the authors found a rotation of nearly 360 degrees during the emergence of a toroidal flux tube. The dependence of the rotation on the amount of twist, present in the emerging field, and the dynamical evolution of the vortical photospheric motions for different emerging field configurations are presently under investigation.…”
Section: Sunspot Tails Separation and Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the twist and the stronger the magnetic tension are, the greater the tube cohesion is and the faster the instability and emergence occur. Numerical studies predict that the emergence process leads to the formation of a new flux-rope and the development of a sigmoidal structure in the corona (see, e.g., Hood et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we consider a different geometry for initial the magnetic field -a toroidal flux tube. This model was originally considered by Hood et al (2009). We shall investigate the behaviour of emerging toroidal tubes through a range of initial field strengths and twists.…”
Section: Introductionmentioning
confidence: 99%